Effect of health education video on knowledge about the first 1000 days of a child's life among women in childbearing age - Anisya Virliana Budiman; Puspa Sari; Sri Astuti; Dini Saraswati Handayani; Didah Didah (Jurnal Kesehatan Ibu dan Anak, 2021)
The first thousand days of life, also known as the golden period, began from conception until the children were 2 years old. This period is critical, so if not utilized properly there will be permanent damage such as impaired physical growth, intelligence, and non-communicable diseases. This study aimed to explore the effect of health education using video media on knowledge about the first 1000 days of life among women of childbearing age. This research uses quantitative methods with a pre-experimental design in the form of one group Pretest-Posttest conducted in July-November 2019. Samples of the research are women of childbearing age in the working area of Jatinangor Public Health Center. Sampling technique with Multistage random sampling with a sample count of 221 respondents. Data analysis using the Wilcoxon test. The results showed that there was an influence on health education by using video media in improving women of childbearing age knowledge about the first 1000 days of life with test result Wilcoxon P = < 0.05 (P = 0,000) and value R = 0,755. There is a health education influence using video media in increasing the knowledge of women of childbearing age about the first 1000 days of life.